PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA MODEL GUIDED INQUIRY UNTUK MELATIHKAN KETERAMPILAN PROSES SAINS DAN MENINGKATKAN HASIL BELAJAR SISWA SMP - Anik Sulistyorini; Tjandrakirana Tjandrakirana; Soetjipto Soetjipto (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research was done by developing science learning materials (lesson plans, students worksheets, students book, and learning achivement test) based on guided inquiry learning model using 4D development model to facilitate students science process skills and improving students learning achivement on environmental pollutions matter. The objective of this research was to trial learning materials in 35 of junior high schools students with one group pretest-postest design. Results were analyzed by descriptive quantitative-qualitative are: (1) Validity of learning material valid category (3.00); (2) Practicalitybased on: a) Feasibility of instruction good category (3,8); b) Readability of worksheets and students book students stating that the content and appearance of worksheets and students book is interesting; c) The response of students very positively (85.6%); (3) Effectiveness based on: a) Students activities who stand out were practice science process skills is high category (38,5%); b) Students science process skill in very high category as shown by students worksheet achivement (3,46); c) student learning achivement increased (N-Gain: 0.2-1.0). The conclusion of this research that science learning material depeloped base on guided inquiry learnig model, eligible to facilitate students science process skills and improve student learning achivement in junior high school. Telah dilakukan penelitian dengan mengembangkan perangkat pembelajaran (RPP, LKS, Materi Ajar, dan Tes Hasil Belajar) model guided inquiry dengan model pengembangan 4D untuk melatihkan keterampilan proses sains pada pokok bahasan pencemaran lingkungan dengan tujuan meningkatkan hasil belajar siswa. Sasaran penelitian adalah perangkat pembelajaran yang diujicobakan pada 35 siswa SMP dengan rancangan One Group Pretest-Postest Design. Kelayakan perangkat pembelajaran yang dikembangkan dianalisis secara deskriptif kuantitatif-kualitatif dengan hasil : (1) Validitas perangkat kategori valid (3,00); (2) Kepraktisan perangkat yang meliputi: a) Keterlaksanaan baik (3,8); b) Keterbacaan LKS dan buku siswa menyatakan bahwa isi LKS dan buku menarik, c) Respon siswa sangat positif (85,6 %); (3) Keefektifan perangkat permbelajaran yang meliputi: a) Aktivitas siswa yang menonjol adalah berlatih keterampilan proses sains dengan kategori tinggi (38,5 %);  b) Hasil keterampilan proses siswa dalam mengerjakan LKS sangat tinggi (3,46); c) Hasil belajar siswa meningkat (N-Gain: 0,2-1,0).  Simpulan penelitian ini adalah perangkat pembelajaran IPA model guided inqury layak untuk melatih keterampilan proses sains dan meningkatkan hasil belajar siswa SMP